A hygroscopic hydrogel and a preparation method and application thereof

By preparing hydrogels with hierarchical pore structures and combining them with the crosslinking of complexing groups, thermally responsive materials, and nanoporous materials, the problem of slow hydrogel kinetics was solved, achieving efficient water vapor adsorption and desorption and improving atmospheric water collection efficiency.

CN120718301BActive Publication Date: 2025-12-26ZHEJIANG NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511240928.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-02
Publication Date
2025-12-26
Estimated Expiration
2045-09-02

AI Technical Summary

Technical Problem

Existing hydrogels exhibit slow water vapor adsorption-desorption kinetics in adsorption-based atmospheric water collection, which limits their application.

Method used

Hygroscopic polymers with complexing groups are crosslinked with thermally responsive hydrophilic-hydrophobic transition materials and nanoporous materials to form hydrogels with hierarchical pore structures. The hydrogels are gelled by adding hygroscopic salts and then freeze-dried to form hydrogels with macroporous structures and nanoporous structures.

Benefits of technology

It achieves ultrafast adsorption-desorption kinetics and high water vapor adsorption capacity, and can still exhibit ultra-high water production even in arid climates, significantly improving water collection performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120718301B_ABST
    Figure CN120718301B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of hygroscopic hydrogel preparation and its atmospheric water collection, and particularly relates to a kind of hygroscopic hydrogel and its preparation method and application, comprising the following steps: hygroscopic polymer with complexing group is dissolved in water, then material with thermal response hydrophilic-hydrophobic transition is added to stir and dissolve, to obtain polymer solution, add nanoporous material with complexing site to polymer solution, complexing group on gel main material and complexing site on nanoporous material with complexing site preliminary crosslinking is carried out, and uniform dispersed gel precursor liquid is formed;Hygroscopic salt is added to gel precursor liquid to gel, and after freeze-drying, hierarchical pore hygroscopic hydrogel with macroporous structure and nanometer micropore is obtained, the hydrogel network prepared by the present application has abundant hierarchical pores, which greatly improves water vapor adsorption-desorption kinetics and water collection performance.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of hygroscopic hydrogel preparation and its atmospheric water collection, and in particular to a kind of hygroscopic hydrogel and its preparation method and application. BACKGROUND

[0002] About two-thirds of the earth's surface is covered by water, about 97.5% is salt water, and only 2.5% is fresh water, and of the 2.5% of fresh water, only 0.3% is surface fresh water, and the available fresh water resources for human direct use are very limited. In the face of the increasingly severe water shortage problem, people continue to research advanced water treatment and water collection technology. Compared with the early fog collection and dew condensation, which requires high relative humidity, the adsorption type atmospheric water collection can realize water collection under low humidity conditions, and the adsorption type atmospheric water collection is abbreviated as SAWH. SAWH uses the hygroscopicity of materials to spontaneously adsorb water vapor from the atmosphere, and then releases water through energy input such as heating and light, has the advantages of wide humidity applicability, dispersion feasibility, energy saving, and is not limited by geographical and climatic conditions, etc., and has broad application prospects. Therefore, SAWH technology is the most promising solution for atmospheric water collection and popularization as a decentralized water collection and supply system.

[0003] Hydrogel is a kind of hydrophilic gel with three-dimensional network structure, which has unique adjustable pore network, relatively high mechanical property and huge swelling capacity, making it an excellent atmospheric water collection adsorbent material. However, although hydrogel has high water adsorption capacity, its water vapor adsorption-desorption kinetics is slow, which limits its application in SAWH field. Therefore, how to prepare a hydrogel material with fast water vapor adsorption-desorption kinetics and high water vapor adsorption capacity is a difficult problem to be solved. SUMMARY

[0004] In view of the above shortcomings of the prior art, the present application provides a kind of hygroscopic hydrogel and its preparation method and application, the present application prepares a kind of hydrogel with hierarchical pore structure, for efficient adsorption type atmospheric water collection, not only has ultrafast adsorption-desorption kinetics, but also has high water vapor adsorption capacity, even in the arid climate conditions still shows ultra-high water production.

[0005] To solve the above technical problems, the technical scheme adopted by the present application is as follows.

[0006] A preparation method of a hygroscopic hydrogel, comprising the following steps:

[0007] Dissolve the hygroscopic polymer with complexing groups in water to obtain a hygroscopic polymer aqueous solution with complexing groups.

[0008] The material with a thermal response hydrophilic-hydrophobic transition is stirred and dissolved in the water solution of the hygroscopic polymer with complexing groups to obtain a polymer solution, and the nanoporous material with complexing sites is added to the polymer solution, the complexing groups on the hygroscopic polymer with complexing groups and the complexing sites on the nanoporous material with complexing sites are preliminarily crosslinked, and the nanoporous structure is introduced to form a uniformly dispersed gel precursor solution.

[0009] The hygroscopic salt is added to the gel precursor solution to gel, and the hygroscopic hydrogel with hierarchical pores and nanopores is obtained after freeze-drying.

[0010] The hygroscopic hydrogel with hierarchical pores prepared by the method has high water vapor adsorption capacity and superfast adsorption-desorption kinetics, and can still exhibit superhigh water production under arid climate conditions, thereby greatly improving the water vapor adsorption-desorption kinetics and water collection performance.

[0011] In a preferred embodiment of the present application, the hygroscopic polymer with complexing groups is sodium alginate, carboxylated starch, polyacrylic acid or sodium polyvinyl sulfonate.

[0012] In a preferred embodiment of the present application, the material with a thermal response hydrophilic-hydrophobic transition is hydroxypropyl cellulose, hydroxypropyl methyl cellulose or poly-n-isopropyl acrylamide.

[0013] In a preferred embodiment of the present application, the nanoporous material with complexing sites is a metal organic framework, a covalent organic framework or a molecular sieve.

[0014] In a preferred embodiment of the present application, the metal organic framework is UiO-66(Zr), MOF-801, MOF-5, ZIF-8, MOF-74, MIL-101(Cr), UiO-67(Zr) or HKUST-1, the covalent organic framework is COF-301 or COF-LZU-1, and the molecular sieve is ZSM-5 or SAPO-34.

[0015] In a preferred embodiment of the present application, the hygroscopic salt is lithium chloride, calcium chloride, magnesium chloride or copper chloride.

[0016] In a preferred embodiment of the present application, the mass ratio of the hygroscopic polymer with complexing groups to water is 100 mg-500 mg:10 mL, the mass ratio of the material with a thermal response hydrophilic-hydrophobic transition to the hygroscopic polymer with complexing groups is 1-4:3, the mass ratio of the nanoporous material with complexing sites to the hygroscopic polymer with complexing groups is 0.5-2:3, and the mass ratio of the hygroscopic salt to the hygroscopic polymer with complexing groups is 1.75-17:3.

[0017] Another object of the present application is to provide a hydrophilic hydrogel prepared by the above method.

[0018] A third object of the present application is to provide an application of the above hydrophilic hydrogel in atmospheric water collection.

[0019] Compared with the prior art, the present application has the beneficial effects that:

[0020] 1. In the present application, a hydrophilic polymer with complexing groups is selected as the main material of the hydrogel, then a material with thermal response hydrophilic-hydrophobic transition is added to configure a polymer solution, then a nanoporous material with complexing sites is added to the polymer solution to prepare a gel precursor solution. In this process, the complexing groups on the main material of the hydrogel and the complexing sites on the nanoporous material are preliminarily crosslinked to form a uniformly dispersed gel precursor solution, and the nanoporous structure is introduced into the gel, further enriching the porosity of the gel. Subsequently, a hydrophilic salt is added to the gel precursor solution to gel, and finally, through the freeze-drying process, the macropores formed during the gelation process are retained, and finally a hierarchical-pore hydrogel with macropores and nanopores is formed. The hydrogel with hierarchical-pore structure prepared by the present application has super-fast adsorption-desorption kinetics and high water vapor adsorption capacity in the adsorption type atmospheric water collection, and even in the arid climate, it still shows super-high water production, greatly improving the water vapor adsorption-desorption kinetics and water collection performance.

[0021] 2. The preparation method of the hydrogel with hierarchical-pore structure in the present application is innovative in that most of the polymers with complexing groups are crosslinked with small molecules or high-valent cations to form hydrogels, such as sodium alginate which is usually crosslinked with calcium ions to prepare hydrogels. However, due to the small molecular size of calcium ions and the extremely fast crosslinking speed with sodium alginate, the calcium alginate gel formed by direct crosslinking in an aqueous solution generally does not have a macroporous structure, resulting in slow water vapor adsorption-desorption kinetics. In the present application, the complexing groups are crosslinked with the complexing sites of the nanoporous material, greatly slowing down the crosslinking speed and avoiding the formation of dense hydrogels. The addition of hydrophilic salt not only improves the water vapor adsorption rate of the hydrogel at low relative humidity, but also induces the aggregation and gelation of the hydrophilic polymer crosslinked with the nanoporous material through the hydrophilic salt, which not only provides a macroporous structure in the hydrogel, but also combines with the rich microporous channels inside the nanoporous material to obtain a hydrogel network with rich hierarchical-pore structure, greatly improving the water vapor adsorption-desorption kinetics and water collection performance. The addition of the polymer with thermal response hydrophilic-hydrophobic transition ability improves the desorption efficiency of the hydrogel. BRIEF DESCRIPTION OF DRAWINGS

[0022] Figure 1In the figure, (a) is a preparation route of the hygroscopic hydrogel, and (b) is a physical map of the hygroscopic hydrogel.

[0023] Figure 2 In the figure, (a) is a powder X-ray diffraction pattern of MIL-101(Cr), LiCl and the hygroscopic hydrogel, (b) is an enlarged view of MIL-101(Cr) and the hygroscopic hydrogel at a diffraction angle of 6 degrees to 20 degrees, wherein the hygroscopic hydrogel is SA300-HPC300-MOF(MIL-101)100-LiCl700.

[0024] Figure 3 In the figure, (a) is a Fourier transform infrared spectrogram of MIL-101(Cr), SA300-HPC300, SA300-HPC300-MOF(MIL-101)100 and SA300-HPC300-MOF(MIL-101)100-LiCl700 in Example 1, (b) is an enlarged view of (a) at a wavelength of 1500 cm -1 nearby.

[0025] Figure 4 In the figure, (a) is a scanning electron microscope image of the SA300-HPC300-MOF(MIL-101)100-LiCl700 hygroscopic hydrogel, (b)-(f) are energy dispersive X-ray spectrograms of the SA300-HPC300-MOF(MIL-101)100-LiCl700 hygroscopic hydrogel.

[0026] Figure 5 Scanning electron microscope images of the SA300-HPC300-LiCl600 hydrogel prepared in Comparative Example 1 at different magnifications.

[0027] Figure 6 Water vapor adsorption-desorption curve diagrams of the hygroscopic hydrogel with different MIL-101(Cr) contents.

[0028] Figure 7 In the figure, (a) is a water vapor adsorption curve diagram of the hygroscopic hydrogel with different LiCl contents, (b) is a desorption curve diagram.

[0029] Figure 8 Water vapor adsorption-desorption cycle diagram of the SA300-HPC300-MOF(MIL-101)100-LiCl700 hygroscopic hydrogel.

[0030] Figure 9 Water vapor adsorption and desorption curve diagrams of the SA300-HPC300-MOF(UiO-66)100-LiCl700 hygroscopic hydrogel.

[0031] Figure 10 Water vapor adsorption and desorption curves for SA300-HPC300-MOF (MOF-801)100-LiCl700 hygroscopic hydrogel.

[0032] Figure 11 Water vapor adsorption and desorption curves for SA300-HPC300-MOF (MOF-5)100-LiCl700 hygroscopic hydrogel.

[0033] Figure 12 Water vapor adsorption and desorption curves for SA300-HPC300-MOF (ZIF-8)100-LiCl700 hygroscopic hydrogel.

[0034] Figure 13 Water vapor adsorption and desorption curves for SA300-HPC300-MOF (MOF-74)100-LiCl700 hygroscopic hydrogel.

[0035] Figure 14 Water vapor adsorption and desorption curves for SA300-HPC300-MOF (HKUST-1)100-LiCl700 hygroscopic hydrogel.

[0036] Figure 15 Water vapor adsorption and desorption curves for SA300-HPC300-Zeolite (ZSM-5)100-LiCl700 hygroscopic hydrogel.

[0037] Figure 16 Water vapor adsorption and desorption curves for SA300-HPC300-Zeolite (SAPO-34)100-LiCl700 hygroscopic hydrogel.

[0038] Figure 17 Water vapor adsorption and desorption curves for SA300-HPC300-COF (COF-301)100-LiCl700 hygroscopic hydrogel.

[0039] Figure 18 Water vapor adsorption and desorption curves for SA300-HPC300-COF (COF-LZU-1)100-LiCl700 hygroscopic hydrogel. DETAILED DESCRIPTION

[0040] The technical solutions in the embodiments of the present application will be clearly and completely described with the preferred embodiments and the accompanying drawings, and it is obvious that the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all the other embodiments obtained by those skilled in the art without creative work fall within the protection scope of the present application.

[0041] It should be noted that all the professional terms used in the present application are only for the purpose of describing the specific embodiments, and are not intended to limit the protection scope of the present application. Unless otherwise specified, the various raw materials, reagents, instruments and equipment used in the following embodiments of the present application can be purchased from the market or prepared by the existing method.

[0042] Embodiment 1

[0043] A preparation method of a hygroscopic hydrogel, comprising the following steps:

[0044] (1) 300 mg of sodium alginate was weighed in a sample bottle, 10 mL of deionized water was added and stirred to dissolve, to obtain a sodium alginate aqueous solution.

[0045] (2) 300 mg of hydroxypropyl cellulose was added to the sodium alginate aqueous solution and stirred to dissolve, to obtain a polymer solution, which was named as SA300-HPC300. Then 100 mg of MIL-101(Cr) was added to the polymer solution and stirred to disperse, to form a uniformly dispersed gel precursor solution, which was named as SA300-HPC300-MOF(MIL-101)100.

[0046] (3) 700 mg of lithium chloride was added to the gel precursor solution and stirred to dissolve, to perform gelation, to obtain a gel precursor. Then the gel precursor was poured into a mold and leveled, and freeze-drying was performed to obtain a hygroscopic hydrogel, which was named as SA300-HPC300-MOF(MIL-101)100-LiCl700.

[0047] Embodiment 2

[0048] A preparation method of a hygroscopic hydrogel, comprising the following steps:

[0049] (1) 300 mg of sodium alginate was weighed in a sample bottle, 10 mL of deionized water was added and stirred to dissolve, to obtain a sodium alginate aqueous solution.

[0050] (2) 300 mg of hydroxypropyl cellulose was added to the sodium alginate aqueous solution and stirred to dissolve, to obtain a polymer solution, and then 100 mg of UiO-66(Zr) was added to the polymer solution and stirred to disperse, to form a uniformly dispersed gel precursor solution.

[0051] (3) 700 mg of lithium chloride was added into the gel precursor solution and stirred to dissolve, and gelation was performed to obtain a gel precursor. Then the gel precursor was poured into a mold and leveled, and lyophilization was performed to obtain a hygroscopic hydrogel, which was named as SA300-HPC300-MOF(UiO-66)100-LiCl700.

[0052] Example 3

[0053] A method for preparing a hygroscopic hydrogel, comprising the following steps:

[0054] (1) 300 mg of sodium alginate was weighed into a sample bottle, 10 mL of deionized water was added and stirred to dissolve, to obtain a sodium alginate aqueous solution.

[0055] (2) 300 mg of hydroxypropyl cellulose was added into the sodium alginate aqueous solution and stirred to dissolve, to obtain a polymer solution. Then 100 mg of MOF-801 was added into the polymer solution and stirred to disperse, to form a uniformly dispersed gel precursor solution.

[0056] (3) 700 mg of lithium chloride was added into the gel precursor solution and stirred to dissolve, and gelation was performed to obtain a gel precursor. Then the gel precursor was poured into a mold and leveled, and lyophilization was performed to obtain a hygroscopic hydrogel, which was named as SA300-HPC300-MOF(MOF-801)100-LiCl700.

[0057] Example 4

[0058] A method for preparing a hygroscopic hydrogel, comprising the following steps:

[0059] (1) 300 mg of sodium alginate was weighed into a sample bottle, 10 mL of deionized water was added and stirred to dissolve, to obtain a sodium alginate aqueous solution.

[0060] (2) 300 mg of hydroxypropyl cellulose was added into the sodium alginate aqueous solution and stirred to dissolve, to obtain a polymer solution. Then 100 mg of MOF-5 was added into the polymer solution and stirred to disperse, to form a uniformly dispersed gel precursor solution.

[0061] (3) 700 mg of lithium chloride was added into the gel precursor solution and stirred to dissolve, and gelation was performed to obtain a gel precursor. Then the gel precursor was poured into a mold and leveled, and lyophilization was performed to obtain a hygroscopic hydrogel, which was named as SA300-HPC300-MOF(MOF-5)100-LiCl700.

[0062] Example 5

[0063] A method for preparing a hygroscopic hydrogel, comprising the following steps:

[0064] (1) Take 300 mg of sodium alginate into a sample bottle, add 10 mL of deionized water and stir to dissolve, to obtain a sodium alginate aqueous solution.

[0065] (2) Add 300 mg of hydroxypropyl cellulose to the sodium alginate aqueous solution and stir to dissolve, to obtain a polymer solution, then add 100 mg of ZIF-8 to the polymer solution and stir to disperse, to form a uniformly dispersed gel precursor solution.

[0066] (3) Add 700 mg of lithium chloride to the gel precursor solution and stir to dissolve, to gel, to obtain a gel precursor, then pour the gel precursor into a mold and flatten, and freeze-dry to obtain a hygroscopic hydrogel, named SA300-HPC300-MOF(ZIF-8)100-LiCl700.

[0067] Example 6

[0068] A method for preparing a hygroscopic hydrogel, comprising the following steps:

[0069] (1) Take 300 mg of sodium alginate into a sample bottle, add 10 mL of deionized water and stir to dissolve, to obtain a sodium alginate aqueous solution.

[0070] (2) Add 300 mg of hydroxypropyl cellulose to the sodium alginate aqueous solution and stir to dissolve, to obtain a polymer solution, then add 100 mg of MOF-74 to the polymer solution and stir to disperse, to form a uniformly dispersed gel precursor solution.

[0071] (3) Add 700 mg of lithium chloride to the gel precursor solution and stir to dissolve, to gel, to obtain a gel precursor, then pour the gel precursor into a mold and flatten, and freeze-dry to obtain a hygroscopic hydrogel, named SA300-HPC300-MOF(MOF-74)100-LiCl700.

[0072] Example 7

[0073] A method for preparing a hygroscopic hydrogel, comprising the following steps:

[0074] (1) Take 300 mg of sodium alginate into a sample bottle, add 10 mL of deionized water and stir to dissolve, to obtain a sodium alginate aqueous solution.

[0075] (2) Add 300 mg of hydroxypropyl cellulose to the sodium alginate aqueous solution and stir to dissolve, to obtain a polymer solution, then add 100 mg of HKUST-1 to the polymer solution and stir to disperse, to form a uniformly dispersed gel precursor solution.

[0076] (3) 700 mg of lithium chloride was added into the gel precursor solution and stirred to dissolve, and the gelation was carried out to obtain a gel precursor, then the gel precursor was poured into a mold and leveled, and the hygroscopic hydrogel was obtained by freeze-drying, and was named as SA300-HPC300-MOF(HKUST-11)100-LiCl700.

[0077] Example 8

[0078] A method for preparing a hygroscopic hydrogel, comprising the following steps:

[0079] (1) 300 mg of sodium alginate was weighed into a sample bottle, 10 mL of deionized water was added and stirred to dissolve, to obtain a sodium alginate aqueous solution.

[0080] (2) 300 mg of hydroxypropyl cellulose was added into the sodium alginate aqueous solution and stirred to dissolve, to obtain a polymer solution, then 100 mg of ZSM-5 was added into the polymer solution and stirred to disperse, to form a uniformly dispersed gel precursor solution.

[0081] (3) 700 mg of lithium chloride was added into the gel precursor solution and stirred to dissolve, and the gelation was carried out to obtain a gel precursor, then the gel precursor was poured into a mold and leveled, and the hygroscopic hydrogel was obtained by freeze-drying, and was named as SA300-HPC300-Zeolite(ZSM-5)100-LiCl700.

[0082] Example 9

[0083] A method for preparing a hygroscopic hydrogel, comprising the following steps:

[0084] (1) 300 mg of sodium alginate was weighed into a sample bottle, 10 mL of deionized water was added and stirred to dissolve, to obtain a sodium alginate aqueous solution.

[0085] (2) 300 mg of hydroxypropyl cellulose was added into the sodium alginate aqueous solution and stirred to dissolve, to obtain a polymer solution, then 100 mg of SAPO-34 was added into the polymer solution and stirred to disperse, to form a uniformly dispersed gel precursor solution.

[0086] (3) 700 mg of lithium chloride was added into the gel precursor solution and stirred to dissolve, and the gelation was carried out to obtain a gel precursor, then the gel precursor was poured into a mold and leveled, and the hygroscopic hydrogel was obtained by freeze-drying, and was named as SA300-HPC300-Zeolite(SAPO-34)100-LiCl700.

[0087] Example 10

[0088] A method for preparing a hygroscopic hydrogel, comprising the following steps:

[0089] (1) Take 300 mg of sodium alginate into a sample bottle, add 10 mL of deionized water and stir to dissolve, to obtain a sodium alginate aqueous solution.

[0090] (2) Add 300 mg of hydroxypropyl cellulose to the sodium alginate aqueous solution and stir to dissolve, to obtain a polymer solution, then add 100 mg of COF-301 to the polymer solution and stir to disperse, to form a uniformly dispersed gel precursor solution.

[0091] (3) Add 700 mg of lithium chloride to the gel precursor solution and stir to dissolve, to gel, to obtain a gel precursor, then pour the gel precursor into a mold and flatten, and freeze-dry to obtain a hygroscopic hydrogel, named as SA300-HPC300-COF(COF-301)100-LiCl700.

[0092] Example 11

[0093] A method for preparing a hygroscopic hydrogel, comprising the following steps:

[0094] (1) Take 300 mg of sodium alginate into a sample bottle, add 10 mL of deionized water and stir to dissolve, to obtain a sodium alginate aqueous solution.

[0095] (2) Add 300 mg of hydroxypropyl cellulose to the sodium alginate aqueous solution and stir to dissolve, to obtain a polymer solution, then add 100 mg of COF-LZU-1 to the polymer solution and stir to disperse, to form a uniformly dispersed gel precursor solution.

[0096] (3) Add 700 mg of lithium chloride to the gel precursor solution and stir to dissolve, to gel, to obtain a gel precursor, then pour the gel precursor into a mold and flatten, and freeze-dry to obtain a hygroscopic hydrogel, named as SA300-HPC300-COF(COF-LZU-1)100-LiCl700.

[0097] Example 12

[0098] A method for preparing a hygroscopic hydrogel, comprising the following steps:

[0099] (1) Take 300 mg of sodium alginate into a sample bottle, add 10 mL of deionized water and stir to dissolve, to obtain a sodium alginate aqueous solution.

[0100] (2) Add 300 mg of hydroxypropyl cellulose to the sodium alginate aqueous solution and stir to dissolve, to obtain a polymer solution, then add 100 mg of MIL-101(Cr) to the polymer solution and stir to disperse, to form a uniformly dispersed gel precursor solution.

[0101] (3) 175 mg of lithium chloride was added into the gel precursor solution and stirred to dissolve, and the gelation was carried out to obtain a gel precursor, then the gel precursor was poured into a mold and leveled, and the hygroscopic hydrogel was obtained by freeze-drying, and was named as SA300-HPC300-MOF(MIL-101)100-LiCl175.

[0102] Example 13

[0103] A method for preparing a hygroscopic hydrogel, comprising the following steps:

[0104] (1) 300 mg of sodium alginate was weighed into a sample bottle, 10 mL of deionized water was added and stirred to dissolve, to obtain a sodium alginate aqueous solution.

[0105] (2) 300 mg of hydroxypropyl cellulose was added into the sodium alginate aqueous solution and stirred to dissolve, to obtain a polymer solution, then 100 mg of MIL-101(Cr) was added into the polymer solution and stirred to disperse, to form a uniformly dispersed gel precursor solution.

[0106] (3) 300 mg of lithium chloride was added into the gel precursor solution and stirred to dissolve, and the gelation was carried out to obtain a gel precursor, then the gel precursor was poured into a mold and leveled, and the hygroscopic hydrogel was obtained by freeze-drying, and was named as SA300-HPC300-MOF(MIL-101)100-LiCl300.

[0107] Example 14

[0108] A method for preparing a hygroscopic hydrogel, comprising the following steps:

[0109] (1) 300 mg of sodium alginate was weighed into a sample bottle, 10 mL of deionized water was added and stirred to dissolve, to obtain a sodium alginate aqueous solution.

[0110] (2) 300 mg of hydroxypropyl cellulose was added into the sodium alginate aqueous solution and stirred to dissolve, to obtain a polymer solution, then 100 mg of MIL-101(Cr) was added into the polymer solution and stirred to disperse, to form a uniformly dispersed gel precursor solution.

[0111] (3) 467 mg of lithium chloride was added into the gel precursor solution and stirred to dissolve, and the gelation was carried out to obtain a gel precursor, then the gel precursor was poured into a mold and leveled, and the hygroscopic hydrogel was obtained by freeze-drying, and was named as SA300-HPC300-MOF(MIL-101)100-LiCl467.

[0112] Example 15

[0113] A method for preparing a hygroscopic hydrogel, comprising the following steps:

[0114] (1) Take 300 mg of sodium alginate into a sample bottle, add 10 mL of deionized water to stir and dissolve, to obtain a sodium alginate aqueous solution.

[0115] (2) Add 300 mg of hydroxypropyl cellulose to the sodium alginate aqueous solution to stir and dissolve, to obtain a polymer solution, then add 100 mg of MIL-101(Cr) to the polymer solution to stir and disperse, to form a uniformly dispersed gel precursor solution.

[0116] (3) Add 1050 mg of lithium chloride to the gel precursor solution to stir and dissolve, to gel, to obtain a gel precursor, then pour the gel precursor into a mold to flatten, to freeze-dry to obtain a hygroscopic hydrogel, named as SA300-HPC300-MOF(MIL-101)100-LiCl1050.

[0117] Example 16

[0118] A method for preparing a hygroscopic hydrogel, comprising the following steps:

[0119] (1) Take 300 mg of sodium alginate into a sample bottle, add 10 mL of deionized water to stir and dissolve, to obtain a sodium alginate aqueous solution.

[0120] (2) Add 300 mg of hydroxypropyl cellulose to the sodium alginate aqueous solution to stir and dissolve, to obtain a polymer solution, then add 100 mg of MIL-101(Cr) to the polymer solution to stir and disperse, to form a uniformly dispersed gel precursor solution.

[0121] (3) Add 1633 mg of lithium chloride to the gel precursor solution to stir and dissolve, to gel, to obtain a gel precursor, then pour the gel precursor into a mold to flatten, to freeze-dry to obtain a hygroscopic hydrogel, named as SA300-HPC300-MOF(MIL-101)100-LiCl1633.

[0122] Comparative Example 1

[0123] A method for preparing a hygroscopic hydrogel, comprising the following steps:

[0124] (1) Take 300 mg of sodium alginate into a sample bottle, add 10 mL of deionized water to stir and dissolve, to obtain a sodium alginate aqueous solution.

[0125] (2) Add 300 mg of hydroxypropyl cellulose to the sodium alginate aqueous solution to stir and dissolve, to obtain a polymer solution, then add 600 mg of lithium chloride to the polymer solution to stir and dissolve, to obtain a gel precursor.

[0126] (3) Then pour the gel precursor into a mold to flatten, to freeze-dry to obtain a hygroscopic hydrogel, named as SA300-HPC300-LiCl600.

[0127] The present application is verified and exemplified by the above several embodiments, but the new method for preparing the macroporous structure and nanometer microporous graded pore hydrogel provided by the present application, the hygroscopic polymer with complexing groups used contains various sodium alginate, carboxylated starch, polyacrylic acid, and sodium polyvinyl sulfonate, and the effects are similar. The material with thermal response hydrophilic-hydrophobic transition used contains various hydroxypropyl cellulose, hydroxypropyl methyl cellulose, and poly-n-isopropyl acrylamide, and the effects are similar. The nanoporous material with complexing sites used is metal organic framework, covalent organic framework, molecular sieve, MIL-101(Cr), UiO-66(Zr), MOF-801, UiO-67(Zr), ZSM-5, SAPO-34, COF-301, MOF-5, etc. The hygroscopic salt used contains various lithium chloride, calcium chloride, magnesium chloride, and copper chloride, and the effects are similar. The mass ratio of the material with thermal response hydrophilic-hydrophobic transition to the hygroscopic polymer with complexing groups is 1-4:3, the mass ratio of the nanoporous material with complexing sites to the hygroscopic polymer with complexing groups is 0.5-2:3, and the mass ratio of the hygroscopic salt to the hygroscopic polymer with complexing groups is 1.75-17:3. The amount of each raw material can be within the above range. The macroporous structure and nanometer microporous graded pore hydrogel of the present application can be prepared using the above raw materials and amounts, and can be used for efficient adsorption type atmospheric water collection. Not only has superfast adsorption-desorption kinetics, but also has high water vapor adsorption capacity.

[0128] The following is an example of the above several embodiments, and the results are analyzed.

[0129] Figure 1 In the above, (a) is a preparation route diagram of the hygroscopic hydrogel; taking SA300-HPC300-MOF(MIL-101)100-LiCl700 as an example, 300 mg of sodium alginate was weighed into a sample bottle, 10 mL of deionized water was added and stirred to dissolve, 300 mg of hydroxypropyl cellulose was added and stirred to dissolve, 100 mg of MIL-101(Cr) was added and stirred to dissolve, 700 mg of lithium chloride was added and stirred to dissolve, then the gel precursor was poured into a mold and flattened, and the hygroscopic hydrogel was obtained by freeze-drying, and the actual picture is shown in (b).

[0130] Figure 2In FIG. 2, (a) is a powder X-ray diffraction pattern of MIL-101(Cr), LiCl and the hygroscopic hydrogel, (b) is an enlarged view of MIL-101(Cr) and the hygroscopic hydrogel at 6 to 20 degrees of diffraction angle, wherein the hygroscopic hydrogel is SA300-HPC300-MOF(MIL-101)100-LiCl700. The characteristic peaks of LiCl are observed in the dried hygroscopic hydrogel, while the diffraction peak intensity of MIL-101(Cr) is low due to the low content. However, the obvious MIL-101(Cr) characteristic peaks can still be observed between 8 to 12 degrees of diffraction angle after enlargement, indicating that the crystal structure of MIL-101(Cr) in the synthesized hygroscopic hydrogel is still maintained.

[0131] Figure 3 In FIG. 3, (a) is a Fourier transform infrared spectrogram of MIL-101(Cr), SA300-HPC300, SA300-HPC300-MOF(MIL-101)100 and SA300-HPC300-MOF(MIL-101)100-LiCl700 in Example 1, (b) is an enlarged view of (a) at a wavelength of 1500 cm -1 nearby. It can be observed that, compared with SA300-HPC300 and MIL-101(Cr), the 1624 cm -1 asymmetric stretching vibration and 581 cm -1 Cr-O characteristic peaks are retained in SA300-HPC300-MOF(MIL-101)100 after the addition of MIL-101(Cr), indicating that the chemical connection of MIL-101(Cr) is not destroyed. In addition, the 1603 cm -1 asymmetric stretching vibration belonging to the carboxyl group in SA300-HPC300 is shifted to 1610 cm -1 in SA300-HPC300-MOF(MIL-101)100, indicating that the carboxyl group of sodium alginate is coordinated with the unsaturated metal sites on the surface of MIL-101(Cr) particles. After the addition of LiCl, the FT-IR spectrogram of the obtained SA300-HPC300-MOF(MIL-101)100-LiCl700 does not change compared with that of SA300-HPC300-MOF(MIL-101)100. In summary, by comparing the FT-IR spectrograms of different samples, it is proved that the carboxyl group on sodium alginate is coordinated with MIL-101(Cr), further proving that the hydrogel preparation mechanism proposed in the present application is correct.

[0132] Figure 4The scanning electron microscope images of SA300-HPC300-MOF(MIL-101)100-LiCl700 hygroscopic hydrogel. (a) is the scanning electron microscope image of SA300-HPC300-MOF(MIL-101)100-LiCl700 hygroscopic hydrogel, (b)-(f) are the energy dispersive X-ray spectroscopy images of SA300-HPC300-MOF(MIL-101)100-LiCl700 hygroscopic hydrogel. The results show that there are abundant macroporous structures in the hydrogel, which is conducive to improving the water adsorption and desorption rate. The four elements C, Cr, Cl and O are uniformly distributed, indicating that LiCl and MIL-101(Cr) are uniformly distributed in the hydrogel.

[0133] Figure 5 The scanning electron microscope images of SA300-HPC300-LiCl600 hydrogel prepared for Comparative Example 1 at different magnifications. The results show that the hydrogel without adding nanoporous materials cannot form abundant macroporous structures in the skeleton. Further, it is shown that the nanoporous materials with unsaturated metal sites or amino end groups are important in the preparation of macroporous hydrogel.

[0134] Figure 6 The water vapor adsorption-desorption curves of hygroscopic hydrogels with different MIL-101(Cr) contents. It can be seen that with the increase of the content of MIL-101(Cr), the water vapor adsorption-desorption rate of the hydrogel is significantly accelerated. The saturated adsorption amount of the hydrogel containing 7.14wt% MIL-101(Cr) is 0.84g·g -1 -1 at 25℃ and air relative humidity RH of 30%. Under the heating condition of 70℃, 0.68g·g -1 of captured water is desorbed in 60min. According to the calculation of desorption for 30min and adsorption for 40min, this material can produce water 15.21L / kg per day. This is because the addition of MIL-101(Cr) to the hydrogel forms macroporous structures, which is conducive to the adsorption and desorption of water vapor. When the content of MIL-101(Cr) in the hydrogel is further increased, it can be found that the adsorption and desorption rate of water vapor of the hydrogel is slower, which is because higher content of MIL-101(Cr) is easy to induce the formation of larger block-shaped gel of the hydrogel solution, thereby hindering the transmission of water vapor, and ultimately reducing the adsorption and desorption rate of water vapor. The SA300-HPC300-LiCl600 hydrogel without MIL-101(Cr) has a lower water vapor adsorption-desorption rate, and the daily water production is only 3.69L / kg.

[0135] Figure 7In the figure, (a) is the water vapor adsorption curve of the hygroscopic hydrogel with different LiCl content, and (b) is the desorption curve. It can be seen that with the increase of the content of lithium chloride, the water vapor adsorption rate of the hydrogel is accelerated, and the water vapor adsorption amount is also gradually increased. This is because with the increase of the added LiCl, the Hofmeister effect generated when the gel is formed is stronger, so that the polymer chains are more likely to aggregate to form a gel network, in addition, lithium chloride has strong hygroscopicity, and the increase of its content will provide more water vapor adsorption sites, thereby not only accelerating the adsorption rate, but also increasing the adsorption amount. When the content of lithium chloride increases to more than 50%, at this time, during the preparation of the gel, a larger amount of gel will be formed due to the stronger Hofmeister effect, thereby increasing the water vapor transmission resistance and reducing the water vapor adsorption and desorption rate.

[0136] Figure 8 The figure is the water vapor adsorption-desorption cycle diagram of the SA300-HPC300-MOF (MIL-101) 100-LiCl 700 hygroscopic hydrogel, and the cycle process is adsorption for 1 hour at 25℃, 30% RH, and then desorption for 1 hour at 70℃. The results show that after 40 cycles, the water vapor adsorption-desorption capacity of the hydrogel does not change much, which proves that the prepared hydrogel has good cycle stability and can be operated for a long time.

[0137] The hygroscopic hydrogel prepared by different materials has a fast water vapor adsorption and desorption rate, and exhibits excellent atmospheric water collection performance, and the data is shown in Table 1.

[0138] Table 1 Daily water production of the hydrogel prepared by different nano-porous materials

[0139]

[0140] Note: Adsorption: 25℃, 30% RH, desorption: 70℃.

[0141] Figures 9-18The water vapor adsorption and desorption curves of the SA300-HPC300-MOF(UiO-66)100-LiCl700, SA300-HPC300-MOF(MOF-801)100-LiCl700, SA300-HPC300-MOF(MOF-5)100-LiCl700, SA300-HPC300-MOF(ZIF-8)100-LiCl700, SA300-HPC300-MOF(MOF-74)100-LiCl700, SA300-HPC300-MOF(HKUST-1)100-LiCl700, SA300-HPC300-Zeolite(ZSM-5)100-LiCl700, SA300-HPC300-Zeolite(SAPO-34)100-LiCl700, SA300-HPC300-COF(COF-301)100-LiCl700 and SA300-HPC300-COF(COF-LZU-1)100-LiCl700 hygroscopic hydrogels prepared by the application are shown in the figures. It can be seen that the hygroscopic hydrogels prepared by using any nanoporous material with complexing sites have fast water vapor adsorption and desorption rates and exhibit excellent atmospheric water collection performance, and the corresponding data are shown in Table 1. The results show that the preparation method of the hygroscopic hydrogel provided by the application has good universality and can be popularized to various nanoporous materials with complexing sites.

[0142] In summary, the hygroscopic polymer with complexing groups is selected as the hydrogel main body material, then the material with thermal response hydrophilic-hydrophobic transition is added to configure the polymer solution, then the nanoporous material with complexing sites is added to the polymer solution to prepare the gel precursor solution. In this process, the complexing groups on the gel main body material will preliminarily crosslink with the complexing sites on the nanoporous material to form a uniformly dispersed gel precursor solution, and the nanoporous structure is introduced into the gel, further enriching the porosity of the gel. Subsequently, the hygroscopic salt is added to the gel precursor solution to gel, and finally, through the freeze-drying process, the macropores formed in the gel process are retained, and finally the hierarchical-pore hydrogel with macroporous structure and nanoporous structure is formed. The hydrogel with hierarchical-pore structure prepared by the application is used for efficient adsorption-type atmospheric water collection, which not only has superfast adsorption-desorption kinetics, but also has high water vapor adsorption capacity, and even in arid climate conditions, it still exhibits superhigh water production, greatly improving the water vapor adsorption-desorption kinetics and water collection performance.

[0143] It is to be understood that every range of values disclosed herein is to be understood to encompass any and every sub-range of values within the range. Although the preferred embodiments of the invention have been described above, it will be appreciated that those skilled in the art, on consideration of this disclosure, will be able to devise additional embodiments that, although not explicitly described or shown herein, nonetheless fall within the scope of the present invention. Accordingly, the appended claims are intended to include within their scope all such alternatives, modifications and variations as fall within the scope of the present invention. Various features and aspects of the present invention will become apparent from the following examples, which are intended only to exemplify the invention. It should be understood, of course, that in the various examples of the present invention, the specific phrasing of the claims will depend on the exact nature of the claims sought.

[0144] Obviously, numerous modifications and variations of the present application are possible in light of the above teachings. It is therefore to be understood that within the scope of the appended claims and their equivalents, the present application can be practiced otherwise than as specifically described herein.

Claims

1. A method for preparing a hygroscopic hydrogel, characterized by, The method comprises the following steps: dissolving a hygroscopic polymer with complexing groups in water to obtain a hygroscopic polymer aqueous solution with complexing groups; adding a material with a thermally responsive hydrophilic-hydrophobic transition to the hygroscopic polymer aqueous solution with complexing groups, stirring and dissolving to obtain a polymer solution, adding a nanoporous material with complexing sites to the polymer solution, and performing preliminary crosslinking between the complexing groups on the hygroscopic polymer with complexing groups and the complexing sites on the nanoporous material with complexing sites, introducing a nanoporous structure, and forming a uniformly dispersed gel precursor solution; adding a hygroscopic salt to the gel precursor solution to gel, and obtaining a hygroscopic hydrogel after freeze-drying; the hygroscopic salt is lithium chloride; the hygroscopic polymer with complexing groups is sodium alginate, carboxylated starch, polyacrylic acid, or sodium polyvinyl sulfonate; the material with a thermally responsive hydrophilic-hydrophobic transition is hydroxypropyl cellulose, hydroxypropyl methyl cellulose, or poly-n-isopropyl acrylamide; the nanoporous material with complexing sites is a metal-organic framework, a covalent organic framework, or a molecular sieve; the mass ratio of the material with a thermally responsive hydrophilic-hydrophobic transition to the hygroscopic polymer with complexing groups is 1-4:3; the mass ratio of the nanoporous material with complexing sites to the hygroscopic polymer with complexing groups is 0.5-2:3, and the mass ratio of the hygroscopic salt to the hygroscopic polymer with complexing groups is 1.75-17:

3.

2. The method for producing a hygroscopic hydrogel according to claim 1, characterized by, the metal-organic framework is UiO-66(Zr), MOF-801, MOF-5, ZIF-8, MOF-74, MIL-101(Cr), UiO-67(Zr), or HKUST-1, the covalent organic framework is COF-301 or COF-LZU-1, and the molecular sieve is ZSM-5 or SAPO-34.

3. The hygroscopic hydrogel prepared by the preparation method according to any one of claims 1-2.

4. The hygroscopic hydrogel according to claim 3 for use in atmospheric water collection.